An Analysis of Compound Words in Education Issue of the Jakarta Post Edition on April 2021 - Dewi Sri Kuning; Fitri Wulandari; Meutia Rachmatia; Sinta Novia (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
In learning a language, the first thing to grasp is words. One method of word formation is compounding, which involves combining two elements from existing words to create a new word. Compounds are categorized into three groups based on the part of speech: nominal compounds, verbal compounds, and adjectival compounds. The formation of compound words gives rise to their meaning, involving two kinds of semantic headedness—namely, endocentric compounds and exocentric compounds. These compound words can be identified in articles from the education issue of The Jakarta Post edition from April 2021. The objectives of this study are as follows: (1) to identify the types of compound words; (2) to determine the semantic headedness of compound words; and (3) to calculate the percentages of compound types and semantic headedness. The study employs a qualitative descriptive method. The results reveal three types of compound words: nominal compounds (656 words), verbal compounds (2 words), and adjectival compounds (5 words). Additionally, two types of compound words were identified—650 words were endocentric compounds, and 16 words were exocentric compounds. The percentages of compound word types were as follows: 98.5% nominal compounds, 0.3% verbal compounds, and 1.2% adjectival compounds. Meanwhile, the percentages of semantic headedness were 97.60% for endocentric compounds and 2.40% for exocentric compounds. This study provides valuable information about compound words in the context of language learning.